Role of resting state MRI temporal latency in refractory pediatric extratemporal epilepsy lateralization. Issue 5 (22nd October 2018) - Shah, Manish N.; Nguyen, Ryan D.; Pao, Ludovic P.; Zhu, Liang; CreveCoeur, Travis S.; Mitra, Anish; Smyth, Matthew D.
Abstract : Background: Pediatric epilepsy affects 0.5–1% of children, with 10–30% of these children refractory to medical anticonvulsant therapy and potentially requiring surgical intervention. Analysis of resting state functional MRI (rsMRI) signal temporal differences (latency) has been proposed to study the pathological cognitive processes. Purpose/Hypothesis: To quantitatively and qualitatively analyze the correlation of rsMRI signal latency to pediatric refractory extratemporal epilepsy seizure foci lateralization. Study Type: Retrospective review. Population: With Institutional Review Board approval, rsMRI and anatomical MRI scans were obtained from 38 registered pediatric epilepsy surgery patients from Washington University and 259 healthy control patients from the ADHD‐200 dataset. Field Strength/Sequence: 3 T echo planar imaging (EPI) blood oxygenation level‐dependent (BOLD) sequence. Assessment: The images were transformed to pediatric atlases in Talairach space. Preoperative voxelwise latency maps were generated with parabolic interpolation of the rsMRI signal lateness or earliness when compared with the global mean signal (GMS) using cross‐covariance analysis. Statistical Tests: Latency z‐score maps were created for each epilepsy patient by voxelwise calculation using healthy control mean and standard deviation maps. Voxelwise hypothesis testing was performed via multiple comparisons corrected (false discovery and familywise error rate) and uncorrected methods to determine significantly late and early voxels. Significantly late and/or early voxels were counted for the right and left hemisphere separately. The hemisphere with the greater proportion of significantly late and/or early voxels was hypothesized to contain the seizure focus. Preoperative rsMRI latency analysis hypotheses were compared with postoperative seizure foci lateralization determined by resection images. Results: Preoperative rsMRI latency analysis correctly identified seizure foci lateralization of 64–85% of postoperative epilepsy resections with the proposed methods. RsMRI latency lateralization analysis was 77–100% sensitive and 58–79% specific. In some patients, qualitative analysis yielded preoperative rsMRI latency patterns specific to procedure performed. Data Conclusion: Preoperative rsMRI signal latency of pediatric epilepsy patients was correlated with seizure foci lateralization. J. Magn. Reson. Imaging 2019;49:1347–1355.